Antimicrobial susceptibility of clinically important carbapenem-resistant Enterobacterales towards standard and new antibiotics - Deniz Hamidov; Emma Keuleyan; Theodor Todorov; Radoslava Vazharova; Georgi Todorov; Atanas Syarov (Journal of Global Antimicrobial Resistance)
AIM: The aim of this work is to study carbapenem-resistant Enterobacterales (CRE) incidence, carbapenemase types and antimicrobial susceptibility of the strains to standard and new antibiotics. BACKGROUND: CRE, carbapenemase–producers, are of critical importance (WHO, CDC), as determinants of difficult to treat infections. Their spread should be controlled and new effective antibiotics are urgently needed. METHODS: During 2023, CRE from patients of the University hospital “Lozenetz” – Sofia were isolated from different clinical specimens and identified by MALDI-tof, Bruker, DE. Susceptibility testing (EUCAST) included Disc diffusion method, MIC determination by Phoenix, BD, USA, or E-tests – Liofilchem, IT. Carbapenemase detection was performed by multiplex real-time PCR according to the ESCMID 2019 protocol. RESULTS: From 720 Enterobacterales isolated, 5.5% were CRE: 35 Klebsiella pneumoniae and 1 of Escherichia coli, Enterobacter cloacae, Enterobacter xiangfangensis, Proteus mirabilis and Providentia stuartii each. All strains were polyresistant, occasionally susceptible to gentamicin, amikacin, co-trimoxazole or fosfomycin. Among carbapenem-resistant Klebsiellae (20%) 8 were colistin resistant. Two strains producing KPC were susceptible to newer antibiotics: ceftazidime-avibactam, imipenem-relebactam, meropenem-vaborbactam, cefiderocole, plazomicin, the remaining demonstrated different rate of susceptibility. Two isolates produced OXA–48 and the rest - metallo-β-lactamases - 31 NDM and 3 VIM type. Antibiotic activity was: cefiderocol > plazomicin > imipenem/relebactam > meropenem/vaborbactam > ceftazidime/avibactam with MIC50 of 0.21mg/L, 1mg/L, 4.5mg/L, 8.5mg/L and 12mg/L respectively. CONCLUSIONS: The high rate of carbapenemase producers with the prevalence of K.pneumoniae with the NDM is particularly worrying: some of the appropriate antibiotics are not available at present in the country.